2005
DOI: 10.1002/jso.20179
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators for carcinoid neuroendocrine tumors of the gastrointestinal tract

Abstract: Factors that determine the clinical course and outcome of patients with gastrointestinal (GI) carcinoid tumors are complex and multifaceted. These include the site of origin within the GI tract, the size of the primary tumor, and the anatomical extent of disease, whether localized, regional, or metastatic to distant sites. The new World Health Organization (WHO) histological classification of endocrine tumors, including carcinoids, represents a significant advance in terms of providing a consistent framework f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(132 citation statements)
references
References 68 publications
(144 reference statements)
8
116
0
7
Order By: Relevance
“…Chromogranin A (CgA) is a secretory product of most NETs and is used as a marker for tumor burden [3]. CS manifests through four key symptoms: flushing (occurs in 94% of patients with CS), diarrhea (78%), cardiac disease caused by valvular heart lesions (53%), and abdominal pain or cramping (51%) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Chromogranin A (CgA) is a secretory product of most NETs and is used as a marker for tumor burden [3]. CS manifests through four key symptoms: flushing (occurs in 94% of patients with CS), diarrhea (78%), cardiac disease caused by valvular heart lesions (53%), and abdominal pain or cramping (51%) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…4 The majority of studies to date have investigated carcinoid tumours as a collective group. [5][6][7][8][9][10] Pulmonary, gastric, and midgut tumours (that include appendiceal tumours in many studies) are heterogeneous, 11 making interpretation of the available results specifically for midgut tumours very difficult. One of the few papers studying the effect of biochemical markers on survival for midgut carcinoid tumours concluded that only chromogranin A and increasing age were independent markers of outcome.…”
mentioning
confidence: 99%
“…As mentioned in the ''Results,'' none of those 4 patients had a documented primary neuroendocrine tumor of another organ in the electronic medical record or pathology database either before or after their surgery. Considering that even JINETs smaller than 1 cm can metastasize, 25 it is possible that the primary tumors were missed intraoperatively by the surgeon. We considered these tumors to most likely represent mesenteric involvement by a primary JINET, but technically the origin was indeterminate because the primary tumor was not identified.…”
Section: Commentmentioning
confidence: 99%